A qualitative exploration of attitudes towards wealth transfer taxation in Australia. Issue 3 (3rd July 2021) - Coram, Veronica
ABSTRACT: Inheritance drives wealth concentration and economic inequality, meaning there is a strong case for wealth transfer taxation as an important element of government redistributive policy. In contrast to many OECD countries, Australia has not had estate or inheritance taxes for 40 years and little is known about contemporary public attitudes towards wealth transfer taxation. This paper draws on qualitative interviews investigating the attitudes of young adult and senior Australians towards wealth transfer taxation. Both groups supported the idea of reintroducing wealth transfer taxation in Australia, largely due to an almost universal absence of expectation that people would or should leave bequests to their descendants. These findings raise the possibility that considering the reintroduction of appropriately targeted wealth transfer taxation in Australia at a time when the Commonwealth Government is experiencing acute fiscal pressures may not generate as much public resistance as might have been assumed.